MARCO, an innate activation marker of macrophages, is a class A scavenger receptor for Neisseria meningitidis. - Mukhopadhyay, S; Chen, Y; Sankala, M; Peiser, L; Pikkarainen, T; Kraal, G; Tryggvason, K; Gordon, S (2006)
The scavenger receptor-A I/II (SR-A) and macrophage receptor with collagenous domain (MARCO) share a common domain organisation and ligand repertoire, including selected polyanions and gram-positive and -negative organisms, but differ in fine specificity of ligand binding, tissue distribution and regulation. Neisseria meningitidis (NM) is a selective ligand for SR-A, but there is evidence for an additional SR-A-independent, polyanion-sensitive component for NM recognition. We therefore studied the relative contribution of MARCO and SR-A to binding of NM by resident and elicited peritoneal macrophages obtained from MARCO-/-, SR-A-/- and SR-A-MARCO-/- mice. Results confirmed that both mouse and human MARCO are able to bind NM independently of NM LPS. MARCO and SR-A contributed independently to NM binding, correlating with their expression levels in different cell populations, but neither of these two molecules was required for release of TNF-alpha and nitric oxide. We propose that the TLR-dependent induction of MARCO by innate immune stimulation enhances recognition and uptake of pathogenic organisms such as NM, thus contributing to host defence against infection.